2004
DOI: 10.1128/iai.72.10.5704-5711.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphatidylinositol 3-Kinase/Protein Kinase B Signaling Pathway Is Activated by Lipoteichoic Acid and Plays a Role in Kupffer Cell Production of Interleukin-6 (IL-6) and IL-10

Abstract: Sepsis caused by gram-positive bacteria lacking lipopolysaccharide (LPS) has become a major and increasing cause of mortality in intensive-care units. We have recently demonstrated that the gram-positive-specific bacterial cell wall component lipoteichoic acid (LTA) stimulates the release of the proinflammatory cytokines in Kupffer cells in culture. In the present study, we have started to assess the signal transduction events by which LTA induces the production of tumor necrosis factor alpha (TNF-␣), interleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
32
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 60 publications
5
32
0
Order By: Relevance
“…In contrast, the production of MCP-1 was found to be independent of p38. Other studies (12) suggest that ERK1/2 is more critical in regulating Kupffer cell IL-6 production compared with p38. The difference between these studies is likely a result of different animal models and different stimuli used but may also reflect the differential regulatory pathways of Kupffer cells following various types of injury.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, the production of MCP-1 was found to be independent of p38. Other studies (12) suggest that ERK1/2 is more critical in regulating Kupffer cell IL-6 production compared with p38. The difference between these studies is likely a result of different animal models and different stimuli used but may also reflect the differential regulatory pathways of Kupffer cells following various types of injury.…”
Section: Discussionmentioning
confidence: 98%
“…The D-alanine content is directly related to the inflammatory potential of LTA. Numerous recent articles have reported that LTA stimulates immune cells to synthesize TNF-α [51], IL-6 [52], IL-8 [53] and nitric oxide [50]. LTA associates with type 2 TLRs and activates kinases such as mitogen-activated protein kinase [54,55] and AKT [52].…”
Section: Discussionmentioning
confidence: 99%
“…These data, coupled with reports that double-knockout Hck 2/2 Fgr 2/2 cells also express higher levels of Fyn, Lyn, and Yes than wild-type cells (27), suggest that functional redundancy might have operated in these early experiments. Furthermore, our group and others have shown that the SFKselective inhibitors PP1 and PP2 inhibit LPS-induced cytokine production (21,26,(28)(29)(30). Thus, an increasing body of apparently contradictory data on the role of SFKs in LPS signaling has now accumulated and deserves to be addressed.…”
mentioning
confidence: 99%